2021
DOI: 10.14738/assrj.85.10246
|View full text |Cite
|
Sign up to set email alerts
|

Remote teaching & digital platform during pandemic Teacher education and teacher competence effects among teachers & principles in Malaysia

Abstract: The purpose of this research is analyzing the opportunities and challenges of emergency remote teaching based on experiences of the COVID-19 emergency among teachers and principals of Malaysian schools.  This study explores the perceptions of school teachers of online learning in a program developed in Malaysian school called School from Home during the COVID-19 Pandemic. A qualitative research method was undertaken in two steps.   In the first step, a thematic analysis a qualitative method was use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This emerging trend towards digitalization and online learning implies the needs for teachers to revise their teaching approaches. As online learning differs greatly from the faceto-face interaction in the classroom, teachers are required to reimagining the teaching and learning process and equip themselves with the necessary digital skills (Ramalingam, et al, 2021). Advanced facilities, such as computer laboratories, smart classrooms, and science laboratories only become beneficial once teachers and students alike know how to effectively utilize the technology and equipment in meaningful ways (Ministry of Education Malaysia, 2013).…”
Section: Literature Review Digital Competence and English Language Le...mentioning
confidence: 99%
“…This emerging trend towards digitalization and online learning implies the needs for teachers to revise their teaching approaches. As online learning differs greatly from the faceto-face interaction in the classroom, teachers are required to reimagining the teaching and learning process and equip themselves with the necessary digital skills (Ramalingam, et al, 2021). Advanced facilities, such as computer laboratories, smart classrooms, and science laboratories only become beneficial once teachers and students alike know how to effectively utilize the technology and equipment in meaningful ways (Ministry of Education Malaysia, 2013).…”
Section: Literature Review Digital Competence and English Language Le...mentioning
confidence: 99%
“…It also investigates the reasons that forced these changes in the roles of teachers and the competencies and skills they must possess (Bader, 2021). The general problems of pedagogical challenges are principally related to the lack of digital skills of teachers and students, the lack of structured content versus the abundance of online resources, the lack of student interactivity and motivation, and the lack of social interaction and teacher learning (Ramanlingam, 2021) From the results of learning observations and interviews with teachers and principals at Tan Nujaba Islamic Elementary School, it was concluded that teachers need the training to help make learning videos, and they need knowledge related to current technological developments in the world of education. In addition, the teachers assessed that learning outcomes in the 2020-2021 school year were quite apprehensive due to the limitations of technological devices.…”
Section: Introductionmentioning
confidence: 99%